El cuento infantil como estrategia pedagógica en la enseñanza y comprensión de la lectura y escritura (2018)
One of the major reforms in education that have been undertaken in accordance with the changes in society and the system of life, is that the teacher adopts the role of facilitator of learning and leaves aside the information transmitter. In terms of reading and writing, many of the students repeat the year because they do not learn to read and write, often due to living conditions or learning difficulties. In the Natania Departmental Technical Educational Institution, the 2nd graders have difficulties in the reading processes, demotivation and lack of interest prevail over learning. It is proposed to use the reading of children's stories as a pedagogical strategy in the learning and comprehension of reading and writing, in an attractive and playful way, and to incorporate the story for the teaching and comprehension of reading and writing and to identify cultural practices, the style and form of communication based on the reading of children's stories The type of research used was descriptive qualitative, with experiential epistemological orientation aimed at a school-type phenomenon and an experimental research design. The outlined objectives were fulfilled to a great extent, the strategies proposed (the story) by teachers and students were accepted, the basic skills of reading skills were strengthened, the group work and the constant participation in the classroom, these actions were evidenced during the time of application of the project